The Role Of Adjudicating Officer With Special Reference To Reality Sector In India: A Critical Appraisal - Praveen, Dr Anil Dawra; Dr. Anjali Sehrawat (Journal of Informatics Education and Research, 2025)
Adjudicating Officer (AO) is a significant adjudicatory functionary under Real Estate Sector in India. It can fine developers, and apply for prompt delivery or refund to ensure the party fulfils the obligations. It is the act of a personality trying to see that the mandatory procedure of RERA 2016 is implemented. That’s provided consumers, hitherto left with few options to make developers accountable without getting into prolonged courtship of expensive litigation, with the much-needed recourse. However, the design and application of the AO system has been limited by its poor performance and stability. Appointment of AOs is at the state level and this might result in different interpretation and enforcement of RERA provisions across regions. Differences in the experience of AOs with respect to expertise have also resulted in differential quality of adjudication as some of them may not have specialisation to deal with complex issues in real estate. Moreover, even if the AO may issue certain orders and penalties, enforcement of these orders is not always easy. Developers may sometimes resist compliance, and enforcement mechanisms are not always robust enough to compel adherence to the AO’s ruling. This article discusses the scope and roles of Adjudicating Officer in terms of implementing the provisions of Act with an aim to bring the promotors in compliance with necessary duties placed upon them. Analysing case studies, legal frameworks, and empirical data, this article reviews how successful the AO has been providing relief to consumers as well as the challenges encountered in dispensing rightness. The results suggests that although the Adjudicating Officer takes an important role in the safeguard of consumer claims, the holdups and differences at state level in the exercise of powers leads to inconsistency in dispute resolution. Recommendations are made to strengthen the role of Adjudicating Officer by providing transparency, responsibility and impartiality in the reality sector and housing market.